Oral Health Behaviors and Oral Health Status in Elementary School Children in East Kalimantan, Indonesia - Andayani, Lia Hapsari; Elisanditya, Amabelle; Soulisa, Abdul Gani; Lestari, Sri (UI Scholars Hub, 2026)
Background: Children's oral health can be influenced by various factors, including health behaviors, dietary patterns, and oral health knowledge. This study aimed to determine the correlation between oral health behaviors and oral health status in elementary school children. Methods: This cross-sectional study involved 182 elementary school children in Bontang, East Kalimantan, taken by convenience sampling. Health behavior data were acquired by 12-item questionnaires based on the WHO guideline. Examination of dental and oral health status was done by using the DMFT Index and OHI-S. Chi-square was used to determine the correlation between oral health behaviors and oral health status. Results: Majority of children had DMFT score index less than or equal to 8 (86.3%) and OHI-S score more than or equal to 1 (54.4%). There was a significant difference between age (p = 0.012) and the dental caries status of children. There was also a significant difference between consumption of biscuits (p = 0.018) and the dental caries status of children. Conclusions: Elementary school children in Bontang, East Kalimantan, still have poor oral health behaviors. Education on the importance of daily toothbrushing, regular dental visits, healthy eating habits, and the use of fluoride-containing toothpaste still needs to be improved.